1992
DOI: 10.1126/science.1279807
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Connection Between the Pores of Distantly Related Ion Channels as Revealed by Mutant K + Channels

Abstract: The overall sequence similarity between the voltage-activated K+ channels and cyclic nucleotide-gated ion channels from retinal and olfactory neurons suggests that they arose from a common ancestor. On the basis of sequence comparisons, mutations were introduced into the pore of a voltage-activated K+ channel. These mutations confer the essential features of ion conduction in the cyclic nucleotide-gated ion channels; the mutant K+ channels display little selectivity among monovalent cations and are blocked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
230
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 469 publications
(242 citation statements)
references
References 41 publications
10
230
0
2
Order By: Relevance
“…No function has yet been demonstrated for either of these proteins [17]. Comparisons of predicted amino acid sequences strongly indicate that both Kv5.1 and Kv6.1 are members of the Kv family [17], exhibiting hallmarks such as the conserved GYGD sequence in H5 [18], six hydrophobic transmembrane domains including the positively charged S4 [19,20], and amino terminal Tl [8] or NA and Nn [17,9] …”
Section: Introductionmentioning
confidence: 99%
“…No function has yet been demonstrated for either of these proteins [17]. Comparisons of predicted amino acid sequences strongly indicate that both Kv5.1 and Kv6.1 are members of the Kv family [17], exhibiting hallmarks such as the conserved GYGD sequence in H5 [18], six hydrophobic transmembrane domains including the positively charged S4 [19,20], and amino terminal Tl [8] or NA and Nn [17,9] …”
Section: Introductionmentioning
confidence: 99%
“…al, 1994), its behaviour is unlike any mechanosensitive channel in eukaryotes and its structure does not resemble any other cloned channel, making it unlikely that it is similar to mechanosensitive channels of eukaryotes. Site-directed mutagenesis studies (Heginbotham et al, 1992) have shown that a two amino acid deletion readily can convert a Kselective channel to a cationic channel, suggesting that stretch-activated K and cationic channels might be closely related. Additionally, permeation studies of stretch-activated cationic channels revealed pore characteristics more like those of a K channel than, for instance, those of ligand-gated non-selective cation channels like the nicotinic acetylcholine receptor (Yang & Sachs, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The pore is most constricted over a narrow span, termed the selectivity filter, which is formed by four loops bearing the amino acid sequence GYG near the extracellular side of the membrane. This sequence is highly conserved throughout the K ϩ channel superfamily and is thought to underlie the basis of K ϩ selectivity; therefore, it is called the K ϩ channel signature sequence (7). Although it is clear that this sequence plays a key role in selectivity, it makes up only a fraction of the channel's entire permeation pathway, and the relative contributions to K ϩ selectivity from the selectivity filter and the rest of the channel pore are still not known.…”
mentioning
confidence: 99%